Anestesia em jundiás (Rhamdia quelen) expostos a substâncias isoladas de plantas - Cunha, Mauro Alves da (2007)
There are some effective anesthetics for fishes, but it is important to search new alternatives of substances easily obtained, of low cost for fish farmers and with no risk to fish and human health. Therefore, this study analyzed the use of some substances extracted from plants as anesthetics, and if efective also evaluating their effects on the stress of silver catfish (Rhamdia quelen). To identify time of induction and anesthetic recovery, silver catfish juveniles were placed in aquaria containing different concentrations of clove oil (Eugenol), essential oils extracted from plants: Chenopodium ambrosioide, Eucalyptus citricola, Calea clematidea, Schinus terebentifolius, Schinus lentiscifolius and Lithraea brasiliensis or extracts obtained from Condalia buxifolia. After induction, fish were transferred to anesthetic-free aquaria to evaluate recovery time. To determine the levels of plasma cortisol, juveniles were exposed to 50mg/L of clove oil or 4mg/L of C. buxifolia methanolic extract and exposed to air for 1 min. Blood was collected 0, 1 and 4 h air exposure and some epecimens were killed at time 0h for sensorial evaluation of the fillet. The results obtained showed that clove oil is a safe alternative as an anesthetic to silver catfish at concentration of 50mg/L, as it reduces plasma cortisol when the fish is exposed to air. However, it leaves a slightly unpleasant taste in the fillet. The C. buxifolia methanolic extract can be used to sedate silver catfish, but it did not induce anesthesia either decrease stress during handling, as it did not alter cortisol levels compared to controls. Other tested substances did not demonstrate any anesthetic effect.